Community Participation in the Planning, Formation and Supervision of BUMDes in Betimus Mbaru Village - Sibolangit - Rolib Sitorus; Japansen Sinaga; Joy Zaman Felix Saragih; Ricky Banke; Andy TM Sihombing; Frederick Xaverius Tjipto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
Village-Owned Enterprises (BUMDes) support village economic development, but community participation in Betimus Mbaru remained limited following the failed pig farming program. This study aims to analyze community participation in the planning, formation, and supervision of Village-Owned Enterprises (BUMDes) in Betimus Mbaru Village, Sibolangit District. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The research informants consisted of the village government, BUMDes administrators, and the people of Betimus Mbaru Village who were involved in the management of BUMDes. The data was analyzed descriptively to determine the form and level of community participation in each stage of BUMDes management. The results of the study showed that community participation in the planning and formation stages of BUMDes was quite good through community involvement in village deliberations, providing ideas, and supporting village business programs. However, the implementation of BUMDes in Betimus Mbaru Village has failed, especially in the livestock development program. The failure was caused by limited human resources (HR), both in terms of knowledge, business management skills, and supervision of BUMDes activities. In addition, low community participation in the supervision stage is also a factor that affects the suboptimal management of BUMDes. Therefore, it is necessary to increase the capacity of human resources through training, mentoring, and strengthening transparency and supervision so that the management of BUMDes can run more effectively and sustainably.